1993
DOI: 10.2307/4002470
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mechanical Treatments and Climatic Factors on the Productivity of Northern Great Plains Rangelands

Abstract: Authors arerangescienrist USDA-ARS, Fort Keogh Livestockand Range Research Loboratory, Miles City, Mont. 59301; research animal scientist USDA-ARS, Forage and Livestock Research Laboratory, El Reno, Okla. 73036; range ecologist USDI-BLM, Oregon State University, Corvallis, Ore. 97331; range scientist and research leader, and range scientist (retired) USDA-ARS, Fort Keogh Livestock and Range Research Laboratory, Miles City, Mont. 59301. Abstract Impacts of 7 range treatments and climate on late spring herbage s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0
2

Year Published

1997
1997
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 17 publications
(23 reference statements)
4
36
0
2
Order By: Relevance
“…Bartos et al (1994) and Cook et al (1994) reported similar results. Other studies have reported an increased forage production after mechanical disturbances in rangelands (Griffith et al, 1985), very likely because of the release of plant nutrients as a result of soil disturbance (Haferkamp et al, 1993). This might be because total ANPP was higher in the Old Field 1 and/or Old Field 2 than in the other disturbance types during most of the study years.…”
Section: Total Annual Net Primary Productivitymentioning
confidence: 64%
“…Bartos et al (1994) and Cook et al (1994) reported similar results. Other studies have reported an increased forage production after mechanical disturbances in rangelands (Griffith et al, 1985), very likely because of the release of plant nutrients as a result of soil disturbance (Haferkamp et al, 1993). This might be because total ANPP was higher in the Old Field 1 and/or Old Field 2 than in the other disturbance types during most of the study years.…”
Section: Total Annual Net Primary Productivitymentioning
confidence: 64%
“…Annual bromes are cyclic in the Northern Great Plains and depend on the amount and distribution of moisture, temperature, and seedbank. 9 Fort Keogh research has demonstrated the potential to severely affect the fertility of annual brome seeds with low-level herbicide treatment. 10 More information on past and current research at Fort Keogh can be found at http://www.ars.usda.gov/Main/docs.…”
Section: Range Researchmentioning
confidence: 99%
“…One early study by the Forest Service in New Mexico (Dortignac and Hickey, 1963) found that runoff and erosion were reduced following contour ripping. In addition, a number of studies have documented the positive effect that contour ripping has on vegetation (Griffith et al, 1985;Haferkamp et al, 1993;Miyamoto et al, 2004;Wight et al, 1978).…”
Section: Introductionmentioning
confidence: 98%